Analysis of Factors that Influence Communities in doing Re-Visit to Outpatient Installation of Praya Hospital Central Lombok - Dhandi Hidayatullah; Nurwijayanti Nurwijayanti; Siti Farida (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
The potential of the hospital includes all the resources owned including all hospital resources as input, management as a process and health service products as an outcome are expected to be able to sell the products produced. In order to remain competitive, the products produced must be of quality and in accordance with the criteria of community needs. In determining target consumers, hospitals need to understand consumer behavior in the decision-making process. The purpose of the study was to analyze the factors that influence the community in conducting outpatient visits at Praya Hospital. The design was Cross Sectional. Population was all patients at the outpatient installation of 1,662 patients. The sample size was 326 respondents using simple random sampling technique. Independent variables of research ware hospital facilities, hospital services, ease of information, ease of access (distance, transportation). The dependent variable was re-visit the outpatient installation. Data was collected using a questionnaire, then the data were analyzed using the ordinal regression test with a significance level of α ≤ 0.05. The results showed that the majority of respondents revealed good hospital facilities as many as 179 respondents (54.9%), good hospital services as many as 184 respondents (56.4%), ease of good information as many as 210 respondents (64%), easy access (distance and transportation) as many as 191 respondents (58.6%), re-visit the outpatient installation as many as 182 respondents (55.8%). The results showed that there were influences of hospital facilities (p = 0,000), hospital services with (p = 0.036), ease of access (p = 0.023), and ease of information (p = 0.001) on revisiting outpatient installations. Hospitals with facilities, easy access and easy information services can increase patient satisfaction so that patients can return to the hospital to make a repeat visit to the outpatient installation